Health-Related Quality of Life and Associated Factors among Male and Female Adolescents in Indonesian Orphanages: A Comparative Study - Aloysia Ispriantari; Rismia Agustina; Zainab Ibrahim Awaulu (Jurnal Keperawatan Soedirman, 2026)
Adolescents living in orphanages face a high risk of health problems, making the assessment of their health-related quality of life (HRQoL) critical. Characterizing gender-based variations in HRQoL is essential to understanding the distinct healthcare needs of this vulnerable population. This study aimed to evaluate gender-specific differences in HRQoL and identify associated factors among adolescents living in orphanages. A total of 238 adolescents (112 males, 126 females) aged 13-18 years were recruited through convenience sampling from 16 orphanages in Malang City, East Java, Indonesia. HRQoL was measured using the KIDSCREEN-27 Child and Adolescent Version, which assesses five dimensions: physical well-being, psychological well-being, autonomy and parent relations, peers and social support, and school environment. Group comparisons were conducted using independent samples t-tests and one-way ANOVA, and multiple-regression analysis was employed to examine factors of HRQoL. Results showed significant gender differences in total HRQoL scores, with females having lower scores than males (p < 0.05). Female adolescents also had lower scores in the physical well-being (p < 0.05) and psychological well-being (p < 0.05) dimensions. Conversely, no significant gender differences were found in autonomy and parent relations, peers and social support, or school environment dimensions. Only age was significantly associated with HRQoL among male adolescents. These findings suggest that female adolescents in orphanages have lower HRQoL scores than their male counterparts, particularly in physical and psychological health. This highlights the importance of incorporating gender-specific considerations in future interventions to improve HRQoL among adolescents living in orphanages.